2014
DOI: 10.1016/j.janxdis.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Swedish posttraumatic stress measures after a disaster

Abstract: This study evaluated the properties of Swedish versions of self-report measures of posttraumatic stress disorder (PTSD), with emphasis on the Impact of Event ScaleRevised (IES-R). Survey data from adult survivors 1, 3, and 6 years after the 2004 Indian Ocean tsunami (n= 1,506) included the IES-R (from which the IES-6 was derived) and the 12-item General Health Questionnaire (GHQ-12). The PTSD Checklist (PCL) was included in one survey. A structured clinical interview was performed after 6 years (n = 142). Fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 47 publications
2
39
0
4
Order By: Relevance
“…We decided to retain the five-factor model because its fit indices best approached the "excellent fit" cutoffs described previously (Byrne, 2009;Hu & Bentler, 1999;Simms et al, 2002). Our findings on the factor structure of the PCL-S are consistent with those of several recent studies (Armour et al, 2012;Arnberg et al, 2014;Pietrzak et al, 2012). In addition, the correlations between the five factors were all very strong, which also coincides with the results of previous studies (Armour et al, 2012;.…”
Section: Discussionsupporting
confidence: 88%
“…We decided to retain the five-factor model because its fit indices best approached the "excellent fit" cutoffs described previously (Byrne, 2009;Hu & Bentler, 1999;Simms et al, 2002). Our findings on the factor structure of the PCL-S are consistent with those of several recent studies (Armour et al, 2012;Arnberg et al, 2014;Pietrzak et al, 2012). In addition, the correlations between the five factors were all very strong, which also coincides with the results of previous studies (Armour et al, 2012;.…”
Section: Discussionsupporting
confidence: 88%
“…The Anhedonia model draws upon theoretical and empirical evidence that besides re-experiencing and avoidance, anxious and dysphoric arousal are two separate symptom clusters (Arnberg, Michel, & Johannesson, 2014; Witte, Domino, & Weathers, 2015), and negative affect and decreased positive affect or anhedonia are two unique constructs (Cuthbert & Kozak, 2013; Watson, 2005, 2009; Watson, Clark, & Stasik, 2011). Importantly, the six clusters of the Anhedonia model represent a further refinement within the clusters of the DSM-5 model for PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…properties of the IES-R, and its screening properties as compared to a structured clinical 18 interview, were examined in a randomly selected subset of participants who had been exposed 19 to the tsunami (Arnberg, Michel, & Johannesson, 2014). According to this study, the IES-R 20 demonstrated excellent psychometric properties as evidenced in longitudinal stability in both 21 its subscales and the screening threshold.…”
mentioning
confidence: 99%